Novel wide-area fault location and predictive maintenance technique for distribution system - Tan C.K.; Ramachandaramurthy V.K. (John Wiley and Sons Inc., 2023)
Locating faults in a power network has been a common chore for utility personnel. However, with the increasing demand in consumer expectations nowadays, fault location time needs to be shortened so that supply can be restored as soon as possible. Considerable amount of time can be saved if an automated mechanism is available to direct the repair crew to the region of fault. Transmission system has already adopted the automated fault location algorithm in their relay. However, implementing such an approach in wide-area distribution network would require huge capital expenditure and resources. This paper presents a reliable, automated fault location algorithm within a wide-area distribution network using a limited number of monitoring devices. In addition, the proposed algorithm is also capable of offering a means of predictive maintenance strategy for the utilities. The algorithm is able to identify the faulted branches in a radial distribution system with high accuracy. In most cases, the calculated fault location is very close to the actual one. This algorithm has also overcome the drawbacks of existing techniques for automated fault location in wide-area distribution network. 2011 Institute of Electrical Engineers of Japan.